Baseline of Surface and Column-Integrated Aerosol Loadings in the Pearl River Delta Region, China - Fan, Xuehua; Xia, Xiangao; Chen, Hongbin; Zhu, Yanliang; Li, Jun; Yang, Honglong; Luo, Hongyan (Frontiers in Environmental Science, 2022)
Much attention has been paid to rapid variation of aerosol loading in the urban areas of the Pearl River Delta (PRD) region. The baseline of aerosol loading in this rapidly developing region is critical in evaluating how and why the aerosol level has evolved, which absolutely requires long-term observations. Based on long-term observations of aerosol optical depth (AOD), visibility, and particulate matter (PM) mass concentrations at Xichong (114.56°E, 22.49°N), a background site in the PRD region, variabilities of aerosol loading at multiple temporal scales are revealed. The means (±σ) of AOD, visibility, PM10, PM2.5, and PM1 are 0.38±0.07, 12.6±2.3 km, 23.7±12.6 μg/m3, 19.7±11.0 μg/m3, and 16.1±10.1 μg/m3, respectively, which show that aerosol loading at Xichong site is much lower than that in urban and suburban sites. Significant decrease in PM10, PM2.5, and PM1 mass concentrations are observed with the magnitudes up to -2.13, -1.82, and -1.37 yr-1, respectively, at 95% confidence level. The decrease of aerosol loadings at Xichong is attributed to the strict environmental regulations for improving air quality. Higher AOD and PM (lower visibility) values are observed during early spring months as a result of long-range transport of biomass burning from Southeastern Asia. Diurnal variation of PM and visibility is dominantly determined by those of boundary layer height and relative humidity. PM mass concentrations show generally negative (positive) correlation with visibility (AOD) at Xichong, but the correlations are weak with the R2 of 0.22 and 0.54, respectively. Low visibility and high aerosol loading is generally associated with very weak easterly and southerly wind. Understanding of variability of surface particle concentration and